SKEMA BONUS DEWAN DIREKSI DAN AKTIVITAS MANAJEMEN LABA PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020 - 2023 - Christina Verawati Situmorang; Duma Megaria Elisabeth (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This study examines the relationship between the Board of Directors' compensation scheme and earnings management practices in the Indonesian banking sector. The main focus is to investigate how bonus components such as distributable profit, operating profit trend, net profit trend, operating profit target, and net profit target affect management behavior in manipulating financial statements. Using multiple regression methods, the study was conducted on 160 banking observations for the period 2020-2023 selected through purposive sampling. Discretionary accruals (DAC) are used as a proxy for earnings management. The results show a significant effect of several bonus components, especially Net Profit Target, on earnings management practices. The findings indicate that an earnings-based compensation scheme can encourage directors to engineer accounting to maximize their bonuses, which underscores the importance of a comprehensive and ethical incentive structure design.